Comparison of the effects of a kinase‐dead mutation of FERONIA on ovule fertilization and root growth of Arabidopsis. Issue 14 (9th July 2018) - Haruta, Miyoshi; Gaddameedi, Vilas; Burch, Heather; Fernandez, Donna; Sussman, Michael R.
Abstract : A plasma membrane receptor protein kinase, FERONIA (FER), regulates various aspects of plant reproductive and vegetative growth. In roots, binding of a peptide ligand to FER causes rapid suppression of cell elongation whereas in ovules, FER is involved in gametophyte interactions. Here, we examined the effect of a mutation that eliminates kinase activity, on both ovule fertilization and root growth, using the same batch of seeds containing a kinase‐dead mutation. The kinase‐dead mutation of FER reduced the ability to complement fer‐4 knockout phenotypes, compared with wild‐type sequence in root, but not in ovules. Our results support a model in which cell type‐specific regulatory mechanisms, such as different interacting partners and/or downstream signaling events, lead to cell type‐specific functions of FER. Abstract : Read the Commentary on this article at doi:10.1002/1873-3468.13184